Disorders, vulnerabilities and resilience in the supply chain in pandemic times - Catarina Ferreira; Catarina Cardoso; Mariana Travassos; Mariana Paiva; Micaela Pestana; Jo\~ao M. Lopes; Márcio José Sol Pereira Oliveira (Logistics, 2021)
The economic and social environment caused by the COVID-19 pandemic has brought additional pressure on supply chains because they now have more pressure to develop and adapt to a context of economic constraint. Delays in the supply chain can bring consequences such as the lack of food products by retailers, transporters and manufacturers. Thus, this study aims to examine the supply chain during the COVID-19 pandemic in small- and medium-sized food companies in the central region of Portugal, identifying potential problems and pointing out the respective solutions. For this purpose, the study uses a qualitative methodology through semi-structured interviews. It was found that small and medium-sized enterprises (SMEs) do not have a codified supply chain and that generally, these companies have a minimal budget, which requires a constant search for new suppliers that represent a reduction in costs. Moreover, most of the companies surveyed faced unexpected challenges, such as a lack of alternative suppliers. The present paper is original because it studies the supply chain in SMEs in the food sector during the COVID-19 pandemic, and it allows the ascertainment of practical suggestions for these companies to improve, as well as contributing to the clarification of the literature on the supply chain in times of crisis such as the current COVID-19 pandemic.
Keywords: 650; supply chain disruptions; SARS-CoV-2/COVID-19 pandemic; small and medium food businesses; supply chain vulnerability and resilience